An Ultraviolet‐Deposited MoO3 Film as Anode Interlayer for High‐Performance Polymer Solar Cells. Issue 6 (6th February 2020) - Cai, Ping; Ren, Peng; Huang, Xiaofang; Zhang, Xiuyun; Zhan, Tao; Xiong, Jian; Xue, Xiaogang; Wang, Zhongmin; Zhang, Jian; Chen, Junwu
Abstract: An ultraviolet‐deposited MoO3 film is developed as anode interlayer based on molybdenum(V) chloride as precursor. The ultraviolet‐deposited MoO3 film is prepared from the precursor film (spin coated from its solution) with ultraviolet irradiation treatment, and the preparation process of the MoO3 film is facile, low cost, and compatible with mass production and flexible substrate. The composition of the MoO3 film is analyzed by X‐ray photoelectron spectroscopy. The work function as well as the surface morphology and wettability of indium tin oxide (ITO) modified by the MoO3 film are investigated by ultraviolet photoelectron spectroscopy, atomic force microscopy, and contact angle tester, respectively, where the analyses show the ITO modified by the MoO3 anode interlayer can offer excellent energy level alignment and interface contact with active layer. The photovoltaic performance of nonfullerene polymer solar cells (PSCs) based on the MoO3 anode interlayer is researched with typical and relatively low‐cost PBDB‐T:ITIC as active layer, and the ITO/MoO3 ‐based device shows the highest power conversion efficiency of 9.27% compared with the bare ITO‐based device (3.69%) and the ITO/PEDOT:PSS‐based device (9.15%). The results demonstrate the great potential of the ultraviolet‐deposited MoO3 film as anode interlayer for high‐performance PSCs. Abstract : An ultraviolet‐deposited MoO3 film is prepared with two simple steps including spin coating and ultraviolet irradiation based on molybdenum(V) chloride as precursor. The polymer solar cells based on the ultraviolet‐deposited MoO3 film as anode interlayer show the highest power conversion efficiency of 9.27% compared with the control devices based on bare ITO (3.69%) and ITO/PEDOT:PSS (9.15%).